Nutritional culture and the level of health awareness among students of the College of Physical Education and Sports Sciences - Sahib, Maha; Juma, Fatima (Journal of Physical Education, 2021)
The study aimed to identify the level of health and nutritional awareness among students of the faculties of physical education (Faculty of Physical Education and Sports Sciences / Al-Jadiriyah Complex, College of Physical Education and Sports Sciences for Girls / Al-Waziriyah, College of Physical Education and Sports Sciences / Al-Farahidi National University), in addition to identifying the differences in the level of awareness To achieve this, the study was conducted on 150 male and female students, 50 male and female students from the College of Physical Education and Sports Sciences (Al-Jadriya Complex), 50 female students from the College of Physical Education and Sports Sciences for Girls (Al-Waziriya), and 50 male students A student from the College of Physical Education and Sports Sciences, Al Farahidi National University, where the sample was randomly selected and a questionnaire was distributed to measure health and nutritional awareness, which consisted of 31 items. After data collection and statistical processing, the results showed a difference in the arithmetic mean of the sample from the hypothetical mean of the health and nutritional awareness scale, where The level of awareness was good, and there were significant statistically significant differences according to the sex variable in favor of males, and no significant differences appeared. According to the educational stage variable and the economic level, and in light of this study, I recommend paying attention to spreading health and nutritional culture among the segments of society through modern means and satellite channels, as well as urging the introduction of health and nutritional awareness within the school curricula and refraining from consuming ready food and soft drinks and replacing them with fresh food and fruits, especially in Nowadays, the trend has become to eat fast foods, especially among university students.